CONSIDERACIONES SOBRE EL PANEGÍRICO XI(3) DEL CORPUS PANEGYRICORUM LATINORUM - Orihuela Sancho, Rebeca (Myrtia, 1996)
The author elucidates to what extent follows Julian’s panegyrist, Claudius Mamertinus, the panegyric genre rules, exposed by the greek rhetor Menander of Laodicea in the third century A.D. On the other hand we have considered of prime interest to compare the panegyric XI(3) to the other laudationes of the ’corpus’, especially to the one from Pliny to Trajan. Following the method proposed by Giuseppina Barabinoy we have divided the laudatio in four parts: proem, praise to the emperor, personal gratefulness and epilogue. Once each of these parts has been examinated, our conclusion is that Mamertinus usually follows the indications of Menander, and its ’laudatio’ is quite similar to the other ones in the ’corpus’. Atthough it is surprising the fact that the panegyrist less similar to Claudius Mamertinus is Pliny.